The role of the church in an urban African society - Dubb, Allie A (Rhodes University, Faculty of Humanities, African Studies, 1961)
This study is based on research carried out in East London, South Africa during the period September 1957 to August 1959 as an Assistant Research Officer of the Institute for Social and Economic Research, Rhodes University. The study is presented in three parts and its theme, broadly speaking, is the role of the church in an urban African society. In Part I, some aspects of the African Church in East London are discussed in general terms and an attempt was made to relate our own material with the findings of other researchers. Emerging from this discussion we have concluded that the Church could potentially play an important part in combating the social disorganization characteristic of urban locations in South Africa, but that on the whole this potential has not been fully exploited.
Keywords: Bhengu, Nicholas B H, 1909-; Pentecostal churches -- South Africa -- East London